Countdown to 2015: Tracking Maternal and Child Health Intervention Targets Using Lot Quality Assurance Sampling in Bauchi State Nigeria. - Dele Abegunde; Nosa Orobaton; Habib Sadauki; Amos Bassi; Ibrahim A Kabo; Masduq Abdulkarim (PLoS ONE, 2015)
Improving maternal and child health remains a top priority in Nigeria's Bauchi State in the northeastern region where the maternal mortality ratio (MMR) and infant mortality rate (IMR) are as high as 1540 per 100,000 live births and 78 per 1,000 live births respectively. In this study, we used the framework of the continuum of maternal and child care to evaluate the impact of interventions in Bauchi State focused on improved maternal and child health, and to ascertain progress towards the achievement of Millennium Development Goals (MDGs) 4 and 5.At baseline (2012) and then at follow-up (2013), we randomly sampled 340 households from 19 random locations in each of the 20 Local Government Areas (LGA) of Bauchi State in Northern Nigeria, using the Lot Quality Assurance Sampling (LQAS) technique. Women residents in the households were interviewed about their own health and that of their children. Estimated LGA coverage of maternal and child health indicators were aggregated across the State. These values were then compared to the national figures, and the differences from 2012 to 2014 were calculated.For several of the indicators, a modest improvement from baseline was found. However, the indicators in the continuum of care neither reached the national average nor attained the 90% globally recommended coverage level. The majority of the LGA surveyed were classifiable as high priority, thus requiring intensified efforts and programmatic scale up.Intensive scale-up of programs and interventions is needed in Bauchi State, Northern Nigeria, to accelerate, consolidate and sustain the modest but significant achievements in the continuum of care, if MDGs 4 and 5 are to be achieved by the end of 2015. The intentional focus of LGAs as the unit of intervention ought to be considered a condition precedent for future investments. Priority should be given to the re-allocating resources to program areas and regions where coverage has been low. Finally, systematic considerations need to be given to the design of strategies that address the demand for health services.